(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to measure and analyze the superior efficiency of industrial companies, which listed in the Iraq Stock Exchange for the period (2017-2019), by using ES-DSM model, and Lingo 18 software, the data of (15) industrial companies were used, this study depend on two approaches they are:(total of assets and total expenses), and two outputs they are: (share price and total revenue).The study explored that there are seven companies that achieved 100% efficiency in 2017, five of them achieved superior efficiency, as (IBPM) which gain first ranked, while (IICM) and (IIEW) ranked last. In 2018, also seven companies achieved an efficiency rate of 100%, five of them also achieved superior efficiency, where (IBSD) ranked first, while (IICM) and (IIEW) ranked last, on the other hand, there were six companies that achieved an efficiency rate of 100% in 2019, four of them achieved maximum efficiency, and the first rank goes to (IBPM) company.And the last rank goes to the companies of both (IICM) and (IIEW), also, IBPM company achieved the first place during the study period, according to ESDSM test, while IBSD ranked at second place, on the other hand, IBSD achieved the first place during (2017-2019), which achieved superior efficiency, while (IBPM) and (IMOS) were in the second place to become the best two companies that other companies can consider them as a typical companies